Low-Dosage Bevacizumab Treatment: Effect on Radiation Necrosis After Gamma Knife Radiosurgery for Brain Metastases - Weng, Yuxiang; Shen, Jie; Zhang, Luyuan; Fang, Zebin; Xiao, Feng; Zhang, Chao; Fan, Zuoxu; Huang, Kaiyuan; Wang, Liyun; Huang, Bin; Wu, Fan; Zhang, Tiesong; et al. (Frontiers in Surgery, 2021)
Cerebral radiation necrosis (RN), a complication of Gamma Knife radiosurgery, is difficult to treat, although bevacizumab seems to be effective. However, clinical data pertaining to bevacizumab treatment for RN are scarce, and its high price is problematic. This study explored the effectiveness of low-dose bevacizumab for RN caused by Gamma Knife. We retrospectively analyzed 22 patients who suffered cerebral RN post-Gamma Knife and received bevacizumab treatment because of the poor efficacy of glucocorticoids. Low-dose bevacizumab (3 mg/kg) was administered for two cycles at 2-week intervals. T1- and T2-enhanced magnetic resonance imaging (MRI) images were examined for changes in RN status. We also monitored the dose of glucocorticoid, Karnofsky Performance Status (KPS) score, and adverse drug reactions. The mean volume of RN lesions decreased by 45% on T1-weighted images with contrast enhancement, and by 74% on T2-weighted images. All patients discontinued the use of glucocorticoids. According to the KPS scores, all patients showed an improvement in their symptoms and neurological function. No side effects were observed. Low-dosage bevacizumab at a dose of 3mg/kg every 2 weeks is effective for treating cerebral RN after Gamma knife for brain metastases.